TRENDS AND INSIGHTS: A BIBLIOMETRIC ANALYSIS OF STUNTING POLICY RESEARCH IN THE SCOPUS DATABASE (2000-2023) - Puspita, Dian Permata; Jatnika, Dyana Chusnulitta; A. Tadda, Muh. Rivaldi (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2025)
This study aims to analyze the bibliographic characteristics and content of stunting policy articles published in Scopus indexed journals by researchers around the world from 2000 to 2023. Data was taken from the Scopus database using the search term "Stunting AND Policy" in various categories, including article title, abstract and keywords. Content analysis and creation of visual representations of keyword occurrences were carried out using the VOSviewer program. This research identified 201 papers on stunting policies published over the last 23 years according to specified protocols. Key topics include stunting, child health, and nutritional status, with publications appearing in 32 journals discussing malnutrition. A collaborative effort involving 37 countries contributes to stunting policy research, and leading journals include Food and Nutrition, World Development, and Food Policy. Institutions in the United States stand out for having the highest number of publications by affiliated researchers. Global research on stunting has experienced significant growth in the last two decades. There is potential for interesting discussions in future research on stunting in relation to public health governance, policy and implementation. However, the limited research in Asia and Africa on this topic underscores the need for further exploration in this region.Bibliometric; Publication; Stunting Policy; Scopus; VOSviewer